O definicji 5 z Księgi V Elementów Euklidesa - Błaszczyk, Piotr (Investigationes Linguisticae, 2007)
It is well known fact that there are two definitions of proportion in Euclid's Elements: Book V, def. 5 and Book VII, def. 20. In the present paper we show that three different interpretations of definition V.5 can be given as modern notation is used: two of them arise from different readings of the definition itself, the third is a negation of disproportion (V, def. 7).